PUBLIC RELATIONS DAN NEW MEDIA (Proses Humas dalam Mengelola Instagram @universitaspertamina) - Sulvinajayanti Sulvinajayanti (Fakultas Ushuluddin, Adab, dan Dakwah IAIN Parepare, 2017)
PR Process in Managing Instagram @universitaspertamina. Instagram is a new media facilitate public relations practitioners in providing information to the public with the aim of providing a positive image. @universitaspertamina is a social media account used by public relations in reaching its external public where the public target is students and academic community which has a range of usage under 40 years. @universitaspertamina is a means of public relations in shaping the image of the organization in front of the public. In Indonesia there are 45 million active citizens using instagram. In practical terms, the instagram function is relevant to the public relations-related external public function. Instagram is a new media facilitate public relations practitioners in providing information to the public with the aim of providing a positive image. @universitaspertamina is a social media account used by public relations in reaching its external public where the public target is students and academic community which has a range of usage under 40 years. @universitaspertamina is a means of public relations in shaping the image of the organization in front of the public.